Peranan Kepemimpinan dalam Menerapkan Prinsip-Prinsip Good Governance di Instansi Pemerintahan Daerah - Kamarasyid, Aloi (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
An attempt to embody a quality, government officials clean and authoritative; the government has set some rules that must be implemented by all the elements government officials who serves as the man of the country and the man of the community. The performance of government agencies in the spotlight from various parties, especially since the reform movement demanding structural change in various fields. In short, today is going on a change from a bad administration pattern at the formation of a good administration. An effort to reach the level of efficiency work organization there needs to be improving performance. There are some things owned by the administration in creating good, so as to be assessed as being successful, his leadership among other: intelligence maturity you, social relations motivation and encouragement, performed sikap-sikap, humanitarian relationship oriented, duty and authority honest and open, demokrastis, and administrative participate and responsible. As for the principles of good governance at least some of the things that must be upheld and performed, namely: accountability, transparency, openness certainty hukum-legalitas, insurance participation, partnership, decentralization professional and proportionate, effective and efficient, productivity and quality of work.